ANALISIS FUNGSI PRODUKSI PADA TANAMAN BAWANG MERAH DI DESA SUNGAI GERINGGING KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR - Amalia '; Hamdan Yasid; Asgami Daughter (Indonesian Journal of Agricultural Economics, 2016)
The purpose of this study was to analyze the factors that influence the production of onion production and analyze the level of cost efficiency onion farm. The method used is a survey method that is applied is interview and observation techniques or direct supervision on the location of the object of the development of the onion. The population used is the onion crop farmers who received assistance onion crop development programs in Kampar Kiri. Overall population sampled, which numbered 40 (forty) persons who are members of the four (4) Farmers Group. The method of analysis to determine the effect of the use of production factors are used red onion analysis model Cobb-Douglass.The results of this study are the factors that influence the production of onion in the village of Sungai Geringging Kampar Kiri District Kampar is the use the use of seeds, land area and the use of dolomite have a positive effect on onion production, production factors use of labor, the use of pesticides and the use of organic fertilizers have a negative impact on production.